Knock-on synthesis of tritopic calix[4]pyrrole host for enhanced anion interactions. Issue 41 (29th July 2019) - Chahal, Mandeep K.; Labuta, Jan; Březina, Václav; Karr, Paul A.; Matsushita, Yoshitaka; Webre, Whitney A.; Payne, Daniel T.; Ariga, Katsuhiko; D'Souza, Francis; Hill, Jonathan P.
Abstract : Anion interactions have been optimized in a tritopic host prepared by using 'knock-on' synthesis of calix[4]pyrrole and their anion binding properties evaluated using different spectroscopic methods. Abstract : Interactions of anionic guests with a tritopic peripherally functionalized conjugated calix[4]pyrrole host (1 ) prepared using a regioselective synthetic method is reported. The regioselectivity of synthesis relies on selective N -alkylation of the calix[4]pyrrole caused by peripheral substitution of one pyrrole group with subsequent N -alkylation at the opposing pyrrole group termed by us 'knock-on' regioselectivity. The resulting host molecule exhibits anion interactions with common chloride and nitrate anions enhanced by an order of magnitude over the parent conjugated calix[4]pyrrole. Combined analysis of 1 H NMR and UV-vis spectroscopic titration data enabled an evaluation of binding strengths of anions with the host K A in a binding model where the salt dissociation process is also incorporated in the form of its dissociation constant K d . Anions could be classified as two types based on their interactions with 1 : Type A anions (chloride, nitrate, perchlorate, hydrogensulphate) associate as 1 : 1 complexes through hydrogen bonding while interactions involving Type B anions (acetate, fluoride, dihydrogenphosphate) are complicated by host deprotonation and/or countercation association. Hosts based on rim-functionalized calix[4]pyrroles such as 1 represent a promising new family of chromophores for estimation of biologically relevant anions or other species.